2019
DOI: 10.1111/iej.13230
|View full text |Cite
|
Sign up to set email alerts
|

Successful pulp revascularization of an autotransplantated mature premolar with fragile fracture apicoectomy and plasma rich in growth factors: a 3‐year follow‐up

Abstract: Aim This case report demonstrates a positive outcome of the adjuvant use of fragile fracture (FF), which is a technique used to harvest dental pulp stem cells (DPSCs), and platelet‐rich plasma (PRP) in a mandibular premolar (tooth 44) with a completely formed root that was transplanted into a surgically created socket and which maintained pulp vitality and function. Summary After virtual surgical planning, a 3D tooth replica of tooth 44 was fabricated. A surgical socket was created in the position of tooth 14;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…As with the replantation of avulsed immature teeth, PCO formation was also observed in impacted incisors when treated by existing surgical methods. Although PCO is considered as a form of pulp revascularization (Tsukiboshi et al, 2019) and a sign of pulp healing (Gavino Orduna et al, 2020; Plakwicz et al, 2015), this condition may be accompanied by yellow discolouration in the crown (Fouad et al, 2020; McCabe & Dummer, 2012), loss of pulpal sensibility (Amir et al, 2001; Gavino Orduna et al, 2020; Oginni et al, 2009) and difficulties when performing further root canal treatment (American Association of Endodontics, (Edited 2010); McCabe & Dummer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As with the replantation of avulsed immature teeth, PCO formation was also observed in impacted incisors when treated by existing surgical methods. Although PCO is considered as a form of pulp revascularization (Tsukiboshi et al, 2019) and a sign of pulp healing (Gavino Orduna et al, 2020; Plakwicz et al, 2015), this condition may be accompanied by yellow discolouration in the crown (Fouad et al, 2020; McCabe & Dummer, 2012), loss of pulpal sensibility (Amir et al, 2001; Gavino Orduna et al, 2020; Oginni et al, 2009) and difficulties when performing further root canal treatment (American Association of Endodontics, (Edited 2010); McCabe & Dummer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, regeneration materials such as platelet-rich plasma (PRP) used as scaffold materials [ 80 ] can be used inside the alveolus of the recipient site in order to favor the revascularization of the transplanted tooth as reported by Gaviño et al (2020) [ 81 ] and also confirmed by a case series on 11 transplanted teeth by Gonzalez-Ocasio and Stevens [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was shown to be effective in dog studies [24][25][26]38], where necrotic pulp tissue was replaced by wellvascularized and cell-rich connective tissue within 90 days in two-thirds of the cases. Three recent case reports proved the feasibility of this approach for single-rooted teeth scheduled for autotransplantation and showed promising initial outcomes [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel surgical technique using extraoral apical resection for preservation of pulp vitality in mature autotransplanted teeth was presented [21]. Subsequently, two case reports have also shown successful outcomes using similar techniques [22,23]. The promising data obtained with this novel approach is corroborated by animal studies, where root-end resection of mature transplants has yielded high revascularization rates [24][25][26].…”
Section: Introductionmentioning
confidence: 99%